Southern Baptist Evangelism of Coptic Christians: Is It Proselytism? - Cheyne, John R. (Transformation, 1991)
Defining the concept of “proselytism” from a Biblical viewpoint, the author attempts to distinguish between witnessing through life-style evangelism and the introduction of the word of God, and overt attempts to draw others away from their historic beliefs, sometimes through questionable methodologies and/or unethical inducements. He points out that when renewal and revival within a body of believers bring about a spontaneous desire to follow Biblical principles, and a different approach toward worship, individuals should have the freedom to make that choice.